2009
DOI: 10.4049/jimmunol.0802928
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Immunogen to Primate M Cells with Tetragalloyl Lysine Dendrimer

Abstract: Effective uptake of Ags by specialized M cells of gut-associated lymphoid tissues is an important step in inducing efficient immune responses after oral vaccination. Although stable nontoxic small molecule mimetics of lectins, such as synthetic multivalent polygalloyl derivatives, may have potential in murine M cell targeting, it remains unclear whether synthetic multivalent polygalloyl derivatives effectively target nonhuman and human M cells. In this study, we evaluated the ability of a tetragalloyl derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Phage display libraries are powerful tools to obtain specific ligands against small molecules, cells, and even tissues (31,(55)(56)(57)(58). Previously, this method has been used to identify M celltargeting ligands using rat PPs, although the identified peptides showed high binding affinity only to mucosa and Caco-2 cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…Phage display libraries are powerful tools to obtain specific ligands against small molecules, cells, and even tissues (31,(55)(56)(57)(58). Previously, this method has been used to identify M celltargeting ligands using rat PPs, although the identified peptides showed high binding affinity only to mucosa and Caco-2 cells (46).…”
Section: Discussionmentioning
confidence: 99%
“…One example is antigen targeting to differentiated microfold (M) cells that normally pass antigens along to underlying DCs and macrophages within mucosal tissues (33,37). Unfortunately, M cells are relatively uncommon compared with the number of less-differentiated columnar epithelial cells that constitute the majority of mucosal surfaces.…”
mentioning
confidence: 99%
“…As shown in Misumi et al. (2009), immunofluorescence analysis demonstrated that M‐like cells in the model showed costaining of an FITC‐labeled tetragalloyl‐ d ‐lysine dendrimer (TGDK) (green) and an anti‐gp2 antibody (red) (Fig. 1b), suggesting that TGDK specifically bound to human M‐like cells.…”
Section: Introductionmentioning
confidence: 97%
“…(2009). The monolayers including M‐like cells or Caco‐2 control monolayers were incubated with FluoSpheres ® carboxylate‐modified microspheres (Life Technologies Corporation, Grand Island, NY).…”
Section: Introductionmentioning
confidence: 99%